RESPON SUPLEMENTASI MINERAL ZINK (Zn) TERHADAP KECERNAAN IN-VITRO RANSUM TONGKOL JAGUNG AMONIASI - Elihasridas Elihasridas (State Islamic University of Sultan Syarif Kasim Riau, 2012)
The present research was conducted to investigate the effect supplementation of mineral zinc on in-vitro digestibilityof ammoniated corn cobs ration. The objective of this experiment is to determine the optimum level of zinc supplementation toin the ration through in-vitro digestibility trial. The rations consisted of 50% ammoniated corn cobs and 50% concentrates.The treatments was various levels of zinc of 0, 50, 100, 150 and 200 mg/kg of ration based on DM basis. Parametersmeasured included digestibility of fiber fractions (NDF, ADF, sellulosa and hemisellulosa). Data were statistically analyzedby variance analysis in a block randomized design. Results showed that the treatmens gave hightly significant (P<0,01) effecton the digestibility. Digestibility of fibers fractions increased as increasing level of zinc supplementation. The bestdigestibility of fibers fractions was found on 100 mg/kg of Zinc supplementation in the ration as dry matter basis